LEGAL CAPACITY AND HUMAN DIGNITY – CRITICAL REMARKS ON INCAPACITATION IN POLISH LAW IN A COMPARATIVE PERSPECTIVE - Andrzej Herbet (Pravni Vjesnik)
The provisions of the Polish Civil Code concerning legal capacity, including the institution of incapacitation, similarly to other countries in the region, have not undergone major changes since their entry into force on January 1, 1965. Over the years the state of medical knowledge, the perception of various mental illnesses and dysfunctions, as well as the social role of people with disabilities have evolved radically. The systemic context – both constitutional and international (conventional) – as well as the legal state-of-play in this area in most Western European countries, including those which were the regulatory model for the Polish legislator, have also changed. Against this background, the Author advocates the need to abolish the institution of incapacitation and replace it with more nuanced and proportionate legal measures that do not interfere as profoundly with legal capacity and thus with legally protected human dignity. This request is finally being realised by the draft law on instruments for supported decision-making of December 9, 2024.